PERILAKU EKONOMI ETNIS CINA DI INDONESIA SEJAK TAHUN 1930-AN - Ali Padang Siregar (Institut Pendidikan Tapanuli Selatan, 2018)
This economic behavior ultimately leads to a business that is safe and neutral in the sense that it does not pose much risk to the safety and well-being of the self. The concrete form of ethnic Chinese economics tends to move in the field of retail and financial, business that is not a big business (because the vital efforts of its management are controlled by the state). Economic behavior that tends to be proactive, in the form of business or family company, has become characteristic of ethnic Chinese in Asian region including Indonesia. This is also supported by ethnic Chinese perception to the identification of ethnic Chinese against state inhabited. Particularly in Indonesia, the ethnic Chinese economic perception is divided between the economic and ethnic Chinese perceptions of